Memory in the wild - Wagoner, Brady, 1980-; Brescó de Luna, Ignacio; Zadeh, Sophie (Niels Bohr professorship lectures in cultural psychology., 2020)
"Venturing out of the laboratory into the wild of natural settings, it becomes untenable to locate memory strictly in the head. Instead, memory appears as a materially extended and socially distributed process, embedded within culture and history. This book explores the complex relations between practices of remembering and the settings in which they are enacted. It advances a novel set of concepts developed from ecological, cognitive, cultural and narrative currents in psychology and further afield to analyze (1) trajectories of autobiographical remembering, (2) the relation between individual and collective memory, (3) memory and cultural transmission, as well as (4) various methodological techniques to investigate memory in the wild"--